Data Mining in Document Management as a form of Intelligent Decision Support - Stančić, Hrvoje (Array, 2002)
The development of a Corporate Intelligent Information System should include the development of a Document Management and Data Mining System as a form of Knowledge Management. The development of a new system is divided into ten phases which are described in detail. Document management system is defined as a system which process digital records containing information through their lifecycle. Documents are stored in huge databases which can range in size into terabytes. Strategic information are hidden within the huge amount of data. Drawing meaningful conclusions out of such a system could be vital as guidence to making important strategic decisions. Therefore, we propose that such a system should be proactive and reactive, and contain data descriptors which are needed in order for the system to classify data, support data analysis, and discovery of patterns and relations between data. Further, this paper describes building of an intelligent prediction model based on derived data patterns. However, to ensure meaningful results, the understanding of data is of vital importance. Data mining within document management system does not replace skilled analysts and managers, but rather gives them a powerful new tool to improve the job they are doing. The whole process of development of an intelligent information system is viewed through the need of a modern corporation to implement intelligent decision support in order to be able to quickly adapt to the fast market changes.